Intra and Extra-Familial Child Sexual Abuse: the Role of Psychopathy - Sousa, Marta (European journal on criminal policy and research, 2024)
The present study analyses the relationship between psychopathic traits, the four facets of psychopathy (i.e., interpersonal, affective, lifestyle, and antisocial), and the type of crime committed (i.e., intrafamilial and extrafamilial child sexual abuse; and nonsexual crimes). The Self-Report Psychopathy Scale - Short Form (SRP-SF) and the Marlowe-Crowne Social Desirability Scale - Short Form were completed by 110 male individuals who sexually offended minors (ISOMs) and 146 individuals convicted for nonsexual crimes. Four binary logistic regression analyses were conducted, controlling for sociodemographic, criminal, and individual variables. ISOMs are less likely to score high in the SRP-SF total score and the interpersonal facet and more likely to score high in the affective facet than individuals with nonsexual crimes. Besides, ISOMs are less likely to have a prior history of alcohol and drug abuse and to have previous contact with the justice system but are more likely to have a history of psychological problems. Therefore, only the prior alcohol and drug abuse history emerged as predictors for ISOMs subtypes. According to our results, psychopathic traits should not be considered in the assessment and intervention of ISOMs, and the focus of the intervention should be on the affective dimension and the level of psychopathology.